Determinants of Foreign Direct Investment in ASEAN-5: Economic, Institutional, and Social Factors - Fadlian, Moch. Rizal; Firmansyah, Muhammad; Rahajeng, Lila Widya (Universitas Pasundan, 2025)
In the era of globalization, foreign direct investment (FDI) plays a crucial role in supporting economic growth and stability in developing countries. The ASEAN region strategically attracts FDI due to its diverse economic, social, and institutional characteristics. This study aims to analyze the influence of internal and external factors on FDI in ASEAN-5 countries from 2003 to 2023. The variables studied include corruption, trade openness, Human Development Index (HDI), and economic growth. Using the panel data regression method with a fixed effect model approach, the analysis results show that economic growth positively and significantly affects FDI. In contrast, trade openness shows a significant negative impact. Conversely, the corruption perception index and HDI show no significant effect. These findings emphasize the importance of economic stability and institutional quality in creating a competitive and sustainable investment climate in the ASEAN region.